Pleasure Ground (Breda : Lokaal 01 Breda, 2010)
Claassen, Willem ; Tas, Nele ; Mulder, Warre ; Rooijmans, Raf ; Houben, Hedwig ; Peters, Jak ; van Gent, Sanne ; Verhees, Sebastiaan ; Greber, Benjamin ; Appelman, Marijke ; Weissenrieder, Johanna ; Tamabayashi, Chisato ; Okon, Ima-Abasi ; Newling, Jack ; Changwon Lee ; Märker, Andreas ; Geeven, Lotte
Engels en Nederlands
Exhibition "Pleasure Ground", Lokaal 01 Breda, 25.02.2010 - 18.06.2010
boek